Sobre una tendencia del deseo femenino en el cine mainstream. la reconstrucción de la identidad en el díptico audiovisual de gravity (2013) y el viento (1928) - Dra. Laura ANTÓN SÁNCHEZ (Fonseca, Journal of Communication, 2023)
In contemporary audiovisual fiction, the action plots starring the female researcher develop one of the most complex and challenging female constellations in the Hollywood universe, the study of which can help us understand how the cultural idea of (becoming) a woman is forged, and what are the possible transformations experienced by this identity model in the history of the audiovisual imaginary.